Modularized Reconfigurable Functional Electromagnetic Surfaces Using Tightly Coupled Antennas and Back-Loaded Radio Frequency Circuits - Boyu Sima; Jiayi Gong; Zhenghu Xi; Shunli Zhang; Ziling Li; Tao Wang; Guoxiao Cheng; Huangyan Li; Xiang Wang; Jianpeng Wang; Zhiyuan Zong (Micromachines)
This paper presents a modularized reconfigurable functional electromagnetic surface (MRFES) for broadband absorption and polarization conversion by using tightly coupled dipole antennas (TCDA) and back-loaded radio frequency (RF) circuits (BLRFC). A dual-polarized antenna array with tight coupling and wide angular scanning characteristics is designed. By loading different RF circuits on the back side of the antenna array’s ground plane, switchable broadband absorption and polarization conversion functions are achieved. The design adopts modularization to facilitate the replacement of back-loaded RF circuits for diverse electromagnetic (EM) control functions. The final design of the tightly coupled antenna array has a thickness of 13.437 mm and a size of 119.5 mm × 119.5 mm. It works in a bandwidth range of 4.14–13 GHz. Upon loading the absorption circuit board, a broadband absorbing electromagnetic (EM) surface is formed, achieving dual-polarization absorption within a bandwidth of 4.14–12.4 GHz. With the polarization conversion circuit board attached, polarization conversion effects are realized within a bandwidth of 4.4–12.9 GHz. Both simulations and experiments verify that the designed EM surface possesses modular reconfigurable functions for broadband absorption/polarization conversion. The proposed design scheme holds promising prospects for applications in active stealth, adaptive camouflage, intelligent communication and other fields.